Mathematical modeling transfers during convective drying of papaya (carica papaya l.) considering the boundary conditions at the leading and trailing edges - Gildas Armel , Fouakeu-nanfack; Fokone Abraham , Tetang; Roger Yannick , Ekani; Nsiewe Maxwell , Tientcheu; Marcel , Edoun; Alexis , Kuitche; Belkacem, Ze-ghmati (International Journal of Engineering and Technology, 2024)
In this study, convective heat and mass transfer during papaya drying in a parallel airflow were simulated. The aim of this work was to con-sider the boundary conditions at the leading and trailing edges in the coupled and simultaneous resolution of the heat and mass transfer equations to better predict papaya drying kinetics. The Luikov equations established for this transfer model were discretized by the implicit finite-difference method and then solved simultaneously using the MATLAB 2014 tool. The drying process was simulated under the influ-ence of drying air conditions and product thickness. The results showed that for the moisture ratio, the mean relative errors were 5.21% and 3.89% for the model without and with boundary conditions set at the leading and trailing edges, respectively. Similarly, the results showed that for product temperature, the mean relative errors were 4.35% and 3.61% for the model without and with boundary conditions set at the leading and trailing edges, respectively. Comparison of the predicted models with the experimental data satisfactorily demonstrated that in-corporating the leading and trailing edge boundary conditions in a transfer model enabled better prediction of drying kinetics than the model without the leading and trailing edge boundary conditions.